Biomass flow and water efficiency of cactus pear under different managements in the Brazilian Semiarid - Lopes, Marcos; Cândido, Magno José; Gomes, Ellen; Pompeu, Roberto Cláudio; Silva, Rodrigo (Revista Ciência Agronômica, 2018)
Balanced fertilization is an important factor in optimizing the growth and productivity of crops. This study aimed to evaluate biomass flow and rain use efficiency in cactus pear cv. Gigante fertilized with combinations of nitrogen (10; 70; 100; 130 and 190 kg ha-1 year-1 N) and phosphorus (10; 70; 100; 130 and 190 kg ha-1 year-1 P2O5), in two harvest frequencies (annual and biennal), in the regions of Quixadá and Tejuçuoca, in Ceará. This was a split-plot randomized block design, with four replicates. In Quixadá and Tejuçuoca, the N and P combinations and harvest frequencies influenced the productions rates of different cladode orders and rain use efficiency in cactus pear. In Quixadá, in the annual harvest, the forage production rate (FPR) was 10.3 kg ha-1 day-1 in the N/P2O5 combination at 190.0/190.0 kg ha-1 year-1 and in the biennal harvest, the maximum FPR was 4.6 kg ha-1 day-1 in the N/P2O5 combination at 114.6/136.8 kg ha-1 year-1. In relation to the annual harvest in the municipality of Tejuçuoca, the maximum FPR was 30.0 kg ha-1 day-1 in the N/P2O5 combination at 137.5/190.0 kg ha-1 year-1 and in the biennal harvest, the maximum FPR observed was 38.0 kg ha-1 day-1 with the N/P2O5 combination of 190.0/33.4 kg ha-1 year-1. The biomass productions rate and rain use efficiency are optimized with the balance of combined levels of nitrogen and phosphorus.